2013
DOI: 10.3171/2012.10.jns12169
|View full text |Cite
|
Sign up to set email alerts
|

Impact of particular antiepileptic drugs on the survival of patients with glioblastoma multiforme

Abstract: Object Glioblastoma multiforme (GBM) is the most common astrocytic brain tumor and carries a dire prognosis. Despite current therapeutic options—surgery, radiotherapy, and chemotherapy—survival varies from 11.3 to 14.6 months. A group of drugs known as histone deacetylase inhibitors (HDIs) has demonstrated a potentially beneficial role in cancer treatment, particularly in combination with other therapies. A drug that exhibits potential as an HDI is sodium valproate (VPA), which is frequently used to treat seiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 15 publications
0
37
0
1
Order By: Relevance
“…In accordance with these results, retrospective (meta-)analysis [24-30] of patient data and a single-armed phase-2 clinical trial [31] suggested prolonged survival of glioblastoma patients receiving VPA. A meta study analyzing the largest cohort (1,800 patients), in sharp contrast, could not confirm that VPA treatment of newly diagnosed glioblastoma patients associates with longer progression-free and overall survival [32].…”
Section: Introductionmentioning
confidence: 59%
“…In accordance with these results, retrospective (meta-)analysis [24-30] of patient data and a single-armed phase-2 clinical trial [31] suggested prolonged survival of glioblastoma patients receiving VPA. A meta study analyzing the largest cohort (1,800 patients), in sharp contrast, could not confirm that VPA treatment of newly diagnosed glioblastoma patients associates with longer progression-free and overall survival [32].…”
Section: Introductionmentioning
confidence: 59%
“…19 Importantly it has recently been shown that GBM patients receiving valproate have extended survival. 20 As salinomycin can increase cytosolic Na + and Ca 2+ levels into the toxic range it is of note that valproate is also a weak blocker of sodium and calcium channels, arguing that normal tissues may be protected against salinomycin toxicity by valproate.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the pharmacological modulators of IK Ca (K Ca 3.1) channels may represent an attractive therapeutic approach to a variety of tumors including gliomas [2,4,9,15,22]. However, whether OXAL or other related drugs exert any effects on the activity of IK Ca channels is not thoroughly understood, despite the fact that it can block K + currents [23].…”
Section: Introductionmentioning
confidence: 99%